Governing for Drought and Water Scarcity in the Context of Flood Disaster Recovery: The Curious Case of Somerset, United Kingdom - Browne, Alison L. (2020)
Historically, flooding has dominated the physical and political landscape of Somerset—particularly over the winter of 2013/2014 when a devastating and high profile flood hit the region. However, the area is also sensitive to drought and water scarcity (D&WS) events—with the region being on the precipice of an increasingly severe drought throughout 2010–2012. This paper focuses on the governance of D&WS in Somerset—one of the six regional case studies in ‘The DROP project’ which explores adaptation and resilience to the climate impacts of drought and water scarcity across North West Europe. The project team visited Somerset twice—once in September 2013 following the period of water scarcity, and again in October 2014 after a period of flooding recovery. The study found on the first visit that there were many positive elements to the regional processes of governance for drought and water scarcity in Somerset. These ranged from the types of instruments and measures used; the extent of the relationships and capacities that were increasingly being built to deal with policies and on-the-ground measures for D&WS; and the increasing visibility of the issue of D&WS for the region after a period of extended dryness. The implications for drought governance in the context of flooding recovery are also discussed, particularly engaging with critical geographical literatures on the emotional and political work underpinning water management in the region, and how such processes are underpinned by broader meta-governance failures in the English water sector.